Melestarikan Islam di Alam Melayu Menerusi Pengajian Ilmu Kalam Berdasarkan Perspektif Ibn Khaldun: Preserving Islam in the Malay World through the Study of Ilm al-Kalam Based on the Perspective of Ibn Khaldun - Ab Hamid, Norafifah; Hamat, Mohd Fauzi; Zainal Abidin, Azmil; Abdul Rahman, Mariam (Jurnal Usuluddin, 2025)
Ilm al-kalam that uses the arguments of reason in convicting the principles of the creed of faith and refute ideologies doubt be viewed as a discipline that can make a significant contribution in preserving Islam in the Malay world, especially at a time when the Muslim community currently inhabiting the region had faced with various challenges of thought and ideology that challenged their beliefs based on the Sunni school of thought. Therefore, the study of ilm al-kalam have highlighted that it is clearly understood by approaches that are relevant in the context of Islam in the Malay community now. This article attempts to examine the concept of ilm al-kalam according to Ibn Khaldun, based on the work of his magnum opus, the Prolegomena and examine the relevance of his thinking about ilm al-kalam now in order to preserve Islam in the Malay world. This study is qualitative by using data collection methods by documentation and data analysis methods by content analysis using deductive and inductive approaches. Among the issues that will be analyzed is the importance of using the aqliyya or rational approach to achieve ma`rifatullah which is the basis of perfection of every Muslim in terms of thinking and the extent to which this approach can be the basis to fortify them from being influenced by ideologies that deviate from Sunni school of thought. This article concludes that an approach that combines the argument of reason with revelation is able to produce ma`rifatullah based on convincing argument and this approach is able to refute the doctrines that deviate from the Sunni based on the school of Asharites. In addition, the study of ilm al-kalam should also emphasize the practical aspect, which is the aspect of appreciation that focuses on the aspect of compliance with the sharia in human life. When this is achieved, then it is definitely going to be able to preserve Islam in the Malay world over the centuries. Several suggestions will also be put forward to strengthen the study of ilm al-kalam in accordance with the current challenges faced by Muslims today.